The Occurrence of Calque in Translation Scripts - Sewell, Penelope (Meta, 2001)
AbstractIt seemed to the author that students were making a larger number of calques when translating from French into English than from English into French.This paper first explores the notion of calque in order to arrive at an operational definition, then identifies and discusses instances of calque in two texts translated under examination conditions, without dictionaries. The students are then divided into categories according to their L1 and observations are made about the amount of calquing exhibited by each group. The results raise a number of questions to which only further research can find an answer.